Kewenangan Pemerintah Daerah Dalam Penertiban Penjualan Dana Pada Fasilitas Umum - Leleury, Glenn Michael Pedro; Nendissa, Renny Heronia; Nirahua, Garciano (Jurnal Saniri, 2024)
Regional governments have an important role in regulating and supervising activities related to public facilities in their area. PUB practices and the sale of funds are regulated at both national and regional levels. However, the problem from a regulatory perspective is that regulations governing PUB practices in public facilities are often unclear and even inadequate.The purpose of this research is to examine and analyze the authority of regional governments and what forms of control can be carried out by regional governments in controlling the sale of funds in public facility areas. With normative juridical research methods and the nature of descriptive analytical writing.The research results show that:1). The government has the authority to regulate the sale of funds at public facilities, further stated in Law no. 23 of 2014 Article 65 paragraph (1) states that regional heads have the task of "maintaining public peace and order". This means that the government has given authority to regional governments to carry out their respective regional affairs, including the maintenance of peace and public order. 2). The form of control carried out by regional governments to handle sales in public facilities is contained in Article 26 paragraph (2) of Minister of Social Affairs Regulation No. 8 of 2021, namely administrative sanctions and criminal sanctions. This includes strict supervision, setting up special zones, using certain regulations. The effectiveness of enforcement strategies varies depending on the context and characteristics of local communities.